Social Construction of Islamic Students and Students of HTN on Islamic State Administration within the Framework of the Pancasila State - Nur Salim; Iwan Jazuli; Aulia Sari (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study analyzes the social construction of Islamic constitutional law students at Sunan Drajat University, Lamongan, regarding the concept of Islamic statecraft (fiqh siyasah) and its relationship to the Pancasila state system. The background of this study departs from the dynamics of the relationship between Islam and the state in Indonesia and the position of students in two scientific traditions, namely Islamic law and positive constitutional law. The purpose of this study is to examine the process of social construction of understanding, the relationship between fiqh siyasah and Pancasila, and the factors that influence it. This study uses a qualitative approach with a phenomenological type. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using Peter L. Berger and Thomas Luckmann's social construction theory through the stages of externalization, objectivation, and internalization. The results show that students' understanding of fiqh siyasah develops from an initial limited understanding to a more conceptual understanding through the academic learning process. The relationship between Islam and Pancasila is understood in a moderate and integrative manner, without conflict, because the values ​​of both are considered harmonious. This social construction is mainly influenced by formal education, supported by the academic environment, Islamic boarding schools (pesantren), and the media. In conclusion, the educational process in the Islamic boarding school environment, which is integrated with higher education, produces a moderate, adaptive, and integrative understanding of the relationship between Islam and the state in Indonesia.